Analyzing the Relationship between Helicobacter Pylori Infection and its Complication in Digestive System Center - abdul-Hussien , Asmaa jabbar; Jawad , Mustafa Kareem (Journal of Science in Medicine and Life, 2025)
Background: Helicobacter pylori infection is a prevalent global health issue, characterized by the bacterium ability to colonize the gastric mucosa and induce chronic inflammation. This spiral-shaped gram-negative bacterium is thought to have evolved to penetrate the stomach mucoid lining, leading to long-term colonization and various gastrointestinal complications. pylori infection is directly associated with peptic ulcer disease, chronic gastritis, gastric cancer. Methodology: A descriptive analytical study was conducted from March 18th, 2025, to July 19th, 2025, to Analyzing the relationship between Helicobacter Pylori Infection and its Complication in digestive system center. A non-probability convenience sample of 100 patients with H. pylori was selected from Al-Diwaniyah teaching Hospital's Digestive System Center. Data collection and analysis were performed using descriptive and inferential statistical procedures. Results: study's findings indicate that the majority of H. pylori patients were females aged 27-37 years, residing in urban areas. Notably, 26 patients held graduate or postgraduate degrees, and half of them were unemployed with moderate socioeconomic status. Gastritis was the most common complication, accounting for 55% of the total cases. Conclusions: The study concludes that patients attending the Gastrointestinal Tract (GIT) center were primarily smokers and did not engage in alcohol or drug abuse, but exhibited poor dietary habits. It is essential to conduct periodic examinations and implement appropriate measures for managing infections consistently and gastritis cases are the most common complications of patients with H. pylori and small ratio (of gastric cancer is associated with h pylori bacterial infection.